Preclinical evaluation of a synthetic peptide vaccine against SARS-CoV-2 inducing multiepitopic and cross-reactive humoral neutralizing and cellular CD4 and CD8 responses. Issue 1 (1st January 2021) - Aparicio, Belén; Casares, Noelia; Egea, Josune; Ruiz, Marta; Llopiz, Diana; Maestro, Sheila; Olagüe, Cristina; González-Aseguinolaza, Gloria; Smerdou, Cristian; López-Díaz de Cerio, Ascensión; Inogés, Susana; Prósper, Felipe; et al.
ABSTRACT: Identification of relevant epitopes is crucial for the development of subunit peptide vaccines inducing neutralizing and cellular immunity against SARS-CoV-2. Our aim was the characterization of epitopes in the receptor-binding domain (RBD) of SARS-CoV-2 spike (S) protein to generate a peptide vaccine. Epitope mapping using a panel of 10 amino acid overlapped 15-mer peptides covering region 401-515 from RBD did not identify linear epitopes when tested with sera from infected individuals or from RBD-immunized mice. However, immunization of mice with these 15-mer peptides identified four peptides located at region 446-480 that induced antibodies recognizing the peptides and RBD/S1 proteins. Immunization with peptide 446-480 from S protein formulated with Freund's adjuvant or with CpG oligodeoxinucleotide/Alum induced polyepitopic antibody responses in BALB/c and C56BL/6J mice, recognizing RBD (titres of 3 × 10 4 –3 × 10 5, depending on the adjuvant) and displaying neutralizing capacity (80–95% inhibition capacity; p < 0.05) against SARS-CoV-2. Murine CD4 and CD8T-cell epitopes were identified in region 446-480 and vaccination experiments using HLA transgenic mice suggested the presence of multiple human T-cell epitopes. Antibodies induced by peptide 446-480 showed broad recognition of S proteins and S-derived peptides belonging to SARS-CoV-2 variants of concern. Importantly, vaccination with peptide 446-480 or with a cyclic version of peptide 446-488 containing a disulphide bridge between cysteines 480 and 488, protected humanized K18-hACE2 mice from a lethal dose of SARS-CoV-2 (62.5 and 75% of protection; p < 0.01 and p < 0.001, respectively). This region could be the basis for a peptide vaccine or other vaccine platforms against Covid-19.